2014
DOI: 10.1002/2014jc010205
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an extreme flood event on optical and biogeochemical properties in a subtropical coastal periurban embayment (Eastern Australia)

Abstract: Major floods impacted the city of Brisbane, eastern Australia, in January 2011, delivering large amounts of dissolved and particulate materials and nutrients into the adjacent coastal embayment, Moreton Bay. The resulting spatially resolved changes in biogeochemical and optical properties in Moreton Bay were examined 1, 2, 6, 19, and 49 weeks after the main freshwater discharge. One week postflood, total suspended matter (TSM) and chlorophyll a (TChla) concentrations varied over 1 order of magnitude throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 62 publications
6
25
0
Order By: Relevance
“…Overall, the relative standard deviation between all triplicates was 8% (N = 57), varying the least for the DH dry season samples (2%) and the most for the VDG dry and wet season samples (13%). Laboratoryestimated particulate inorganic (PIM) and organic (POM) matter fractions of TSS were only available for the 2012 wet season samples and were extracted as described in Oubelkheir et al (2014).…”
Section: Total Suspended Solidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the relative standard deviation between all triplicates was 8% (N = 57), varying the least for the DH dry season samples (2%) and the most for the VDG dry and wet season samples (13%). Laboratoryestimated particulate inorganic (PIM) and organic (POM) matter fractions of TSS were only available for the 2012 wet season samples and were extracted as described in Oubelkheir et al (2014).…”
Section: Total Suspended Solidsmentioning
confidence: 99%
“…The tidal range in their study region was comparable (∼3 m) to that observed during our study of the VDG. Oubelkheir et al (2014) also emphasized the role of short-term processes, such as wind stress and tides, as key drivers of the dissolved and particulate material in the shallow and dynamic subtropical environment of Moreton Bay (SE Queensland). In our study, the sampling strategy was primarily to ensure our stations had a large spatial distribution rather than to sample the small-scale temporal variability due to the tides, thus the tidal phase was not taken into account.…”
Section: Effect Of Local and Seasonal Forcingmentioning
confidence: 99%
“…Samples collected from V3 and PHNRS were analysed using a fibre optic UV/VIS spectrometer (Ocean Optics, Florida, USA) as in Robinson et al (2014). Samples collected from V1, V2 and V4 were measured using a dual beam scanning spectrophotometer equipped with an integrating sphere (GBC 916 UV/VIS; Oubelkheir et al, 2014). Absorption (a(λ)) at wavelengths between and 700 nm (m -1 ) was calculated using equation 14of Tassan and Ferrari (1995).…”
Section: Bio-optical Parametersmentioning
confidence: 99%
“…The satellite phytoplankton absorption coefficient was derived from the Generalised IOP DC model which has demonstrated a high percentage (> 80 %) of valid retrievals of a PHY in waters of all trophic levels and across all seasons (Werdell et al, 2013). Although the GIOP DC was applied to optically complex waters (Cherukuru et al, 2016;Oubelkheir et al, 2014) and without local atmospheric correction, the GIOP-DC uncertainty product for a PHY (443) indicates generally low uncertainty across the 2003-2015 time-series of a PHY (443) retrievals at Port Hacking and Yongala NRS. Within the 589 weeks of a PHY (443) observations at Port…”
Section: Potential For Further Application Of An Absorption-based Satmentioning
confidence: 99%
“…We focused our investigation to the open-sea domain, i.e. we neglected the areas which are more directly affected by bottom and riverine dynamics (e.g., Oubelkheir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%